Using Smartphone in the ESL Classroom Improves Students’ Vocabulary Acquisition via Kahoot! - Jusoh, Juhari Sham (School of Social Sciences, USM, 2017)
This paper is aimed to investigate and demonstrate the positive impact of using smartphone through Kahoot! game-based platform in the English Language Classroom to improve students’ English vocabulary acquisition. The current development in Malaysian education field, 21st century learning style is more focused and given importance. Specifically, the game-based learning platform such as Kahoot! through its capability can create a meaningful learning environment. Vocabulary acquisition was measured in terms of reading passage assessments. The sample of 30 students of diploma level from a college participated in this study. Antonym and Synonym with Contextual Clues were parts of the items in the assessment. Results indicated that all students improved their vocabulary assessment scores in the game-based quiz Kahoot! was played. The use of Kahoot! also increased students’ participation and involvement in ESL classroom. The results of the student satisfaction survey indicated that students enjoyed using their smartphone in the classroom during the lesson and playing the gamebased quiz Kahoot!. They found this Students Response System is easy to use.